2007
DOI: 10.1001/archderm.143.12.1543
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Skin Aging in Identical Twins

Abstract: Background: A twin pair can provide a rare opportunity to control for genetic susceptibility and exposure variables, which often serve as major confounders in population-based studies on the relationship between smoking and skin aging.Observations: We describe a unique twin pair who spent not only their first 2 decades of life together but also in their later decades had the same type of job at the same latitude, resulting in well-matched levels of significant sun exposure. However, the twins differed markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 25 publications
(28 reference statements)
2
34
0
3
Order By: Relevance
“…Also, in 2007 D.Doshi et al [4] describe that identical twins with an approximately 52.5 pack-year smoking history showed more severe skin aging than did the nonsmoking twin. Moreover, Emster V et al [5] (1995) and Patricia M. O'Hare et`al [6] (1999) revealed that smoking increases the risk of facial wrinkles two to threefold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in 2007 D.Doshi et al [4] describe that identical twins with an approximately 52.5 pack-year smoking history showed more severe skin aging than did the nonsmoking twin. Moreover, Emster V et al [5] (1995) and Patricia M. O'Hare et`al [6] (1999) revealed that smoking increases the risk of facial wrinkles two to threefold.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of this phenomenon however, is still unclear. Several studies show that smoking cigarettes is one of the significant causes of facial aging and wrinkling [4,5,6]. The overall literature indicates that those who smoke have a higher risk of developing premature facial wrinkling as compared to those who do not smoke [7].…”
Section: Introductionmentioning
confidence: 99%
“…never smokers. Perhaps the most interesting evidence of this conclusion is illustrated in Doshi, Hanneman, and Cooper's (2007) case study of 52-year-old identical twins. During their childhood and adulthood, the twins lived in the same locations and had similar sun exposure.…”
Section: Figurementioning
confidence: 92%
“…37,38 Finally, our finding that cigarette smoking is associated with higher photodamage (P=.046) is consistent with most of the data in the literature. [9][10][11][12]18,39 Cigarette smoke induces matrix metalloproteinases in the skin and inhibits procollagen synthesis through alteration of transforming growth factor ␤. [40][41][42] This study is one of the few twin studies examining the relationship between environmental factors and photodamage.…”
Section: Commentmentioning
confidence: 99%